SPATIAL AND TEMPORAL ANALYSIS OF ROAD TRAFFIC CRASHES ALONG KANO-MAIDUGURI ROAD - Lawan, I.; Falola, J. A.; Ibrahim, A.; Mustapha, A. (FUDMA JOURNAL OF SCIENCES, 2023)
One of the major challenges in the today’s world is the increased rate of Road Traffic Crashes (RTC) and its casualties on our roads which are becoming worse and more devastating, claiming lives and properties by the day. This paper is aims to explore the spatial and temporal patterns of RTC between Kano-Wudil on Kano-Maiduguri Road. The study uses RTC monthly data for 2010, 2011, 2012, 2013 and 2014 obtained from Policy, Research and Statistics Department of FRSC and uses multiple linear regressions, descriptive tool and GIS to demonstrate the result of the findings. The results reveal that, Gano is a major hotspot with 57 RTC accounted for 15.6% and majority of the RTC (80%) took place during the day time. The conclusion was that, increase rate of RTC has a positive correlation with explanatory variables human and mechanical causes. It is recommended that, there is need for effective placement of road furniture between Gano to Nigeria Police Academy (POLAC) as the more accident prone corridor for helpful sensitisation.
Keywords: Road traffic crashes, operation corridors, patterns, hotspots, Federal Road Safety Commission